2009
DOI: 10.1167/iovs.08-1789
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of Automated Perimetry: A Comparison between Standard Automated Perimetry with Stimulus Size III and V, Matrix, and Motion Perimetry

Abstract: Variability of Matrix and Motion perimetry does not increase as substantially as that of SAP III in damaged areas of the visual field. Increased sampling with the larger stimuli of these techniques is the likely explanation for this finding. These properties may make these stimuli excellent candidates for early detection of visual field progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
153
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(156 citation statements)
references
References 31 publications
3
153
0
Order By: Relevance
“…[18][19][20][21] A larger stimulus could be used for all testing, or the stimulus size could be increased when testing is being conducted at damaged visual FIGURE 3. The contrasts (dB) that would give 50% (left) or 25% (right) response probability for each stimulus size, based on the fitted frequency-of-seeing curves, at each location tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20][21] A larger stimulus could be used for all testing, or the stimulus size could be increased when testing is being conducted at damaged visual FIGURE 3. The contrasts (dB) that would give 50% (left) or 25% (right) response probability for each stimulus size, based on the fitted frequency-of-seeing curves, at each location tested.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17] Previously it has been suggested that use of a size V (1.728 diameter) stimulus could also reduce variability, allowing reliable visual field testing to be performed later into the disease process. [18][19][20][21] This study examines whether the reduction in variability observed when using size V stimuli can be explained solely by the increase in sensitivity, or whether the reliable stimulus range is also extended to higher contrasts than when using size III stimuli. The results from this study will help clinicians, researchers and manufacturers understand the most reliable testing strategies for glaucoma patients with moderate to severe visual field loss, who have the most variable results and also the highest risk of permanent visual impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it may be presumed that increased RT may be a predictor of increased variability and fatigue. In static perimetry, RT in glaucomatous visual field loss increases when the stimulus is closer to threshold [38] and it depends primarily on the slope of the frequency of the seeing curve for that test location and on the frequency of false-positive and false-negative responses [6] . RT, as determined by SKP, increases with increasing eccentricity of the origin of the vector in healthy individuals [24] and in patients with advanced visual field loss [23] .…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Increased test-retest variability is not present for frequency-doubling perimetry, which uses large, sinusoidal stimuli. [11][12][13][14][15] Knowledge about why frequency-doubling stimuli have this property could help identify a wider range of potential new stimuli for perimetry with improved test-retest variability near and within glaucomatous defects.…”
Section: Introductionmentioning
confidence: 99%
“…12,13,26 It is possible that the size of sinusoidal stimuli, rather than their property of being sinusoidal, is the source of reduced variability. For instance, variability in glaucomatous defects can also be reduced 15 by using the size V stimulus, which is has a width of 1.78. However, size alone may not be sufficient to reduce variability because even size V and frequency-doubling stimuli have been found to have an effective dynamic range that is smaller than the range of possible stimulus contrasts provided by the instrument.…”
Section: Introductionmentioning
confidence: 99%